Breeding for Integrated Pest Management (B-IPM): a new concept simultaneously optimising plant resistance and biocontrol - Iqbal, Mudassir; Flöhr, Adam; Andreasson, Erik; Stenberg, Johan A. (Frontiers in Plant Science, 2025)
Plant breeding for disease resistance typically focuses on the traits that target pathogens, although such traits may antagonise beneficial microbes, thus thwarting any opportunities for biocontrol. In this paper, we propose the concept of Breeding for Integrated Pest Management (B-IPM) which requires the simultaneous optimisation of plant traits that confer resistance to pathogens and facilitation of biocontrol agents. We tested the prospects for B-IPM by screening wild strawberry (Fragaria vesca) genotypes for resistance to the detrimental pathogens Botrytis cinerea (causing grey mould disease) and Colletotrichum acutatum (causing anthracnose disease) and facilitation of the beneficial biocontrol agent Aureobasidium pullulans. The plant genotypes showed strong variation in their resistance to the two pathogens and their ability to facilitate biocontrol. However, while the resistance of plant genotypes to both pathogens was strongly correlated, there was no correlation between this and facilitating biocontrol, suggesting that resistance and biocontrol facilitation can be independently optimised to prepare plants for pesticide-free farming.